Evaluasi Waktu Tunggu Pelayanan Resep Obat Racikan dan Non Racikan pada Pasien Rawat Jalan di Apotek - Depi Yuliana; Faizul Bayani; Dedent Eka Bimmaharyanto; Lelie Amalia Tusshaleha; Syamsul Rahmat; Meilynda Pomeistia; Recta Olivia Umboro (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The quality of health services is still not optimal, especially in terms of patient dissatisfaction with drug services at pharmacies. A more efficient system can be built only if the waiting time evaluation has been carried out at pharmacies that provide drug prescriptions for patients. This study aims to evaluate the waiting time for prescription services at pharmacies to achieve patient satisfaction with drug services at pharmacies. In this study, Angkasa Farma's pharmacy became the subject of evaluation. The study was conducted with an observational design using descriptive analysis. The waiting time data obtained were then analyzed descriptively and compared with the minimum service standard of waiting time, this is for two types of drugs (prepared drugs and compound drugs). The results of the study based on a sample of 100 recipes and 100 non-concoction recipes are the number of recipes that meet the standards for prescription recipes as many as 37 recipes and for non-concoction recipes as many as 95 recipes. The average waiting time for concoction recipe services is 41.47 minutes and the average waiting time for non-concoction prescription services is 21.29 minutes. The average waiting time for non-concoction prescription services has met the standard, while the waiting time for blended prescription services has not met the standards according to the Regulation of the Minister of Health of the Republic of Indonesia.